Analisis Kesulitan Guru dalam Mengembangkan Rencana Pembelajaran untuk Meningkatkan Penalaran Matematis Siswa - Rahma Nasir; Uncok Manigor Jokkas Siahaan; Fajriani Fajriani (Jurnal Kreatif Online, 2022)
Lesson preparation is a challenging job. Researchers and educators worldwide generally agree that a lesson plan's quality and an efficient teaching-learning process go hand in hand. Meanwhile, mathematical reasoning aids in the development of logical reasoning and critical thinking in mathematics. Inadequate mathematical thinking abilities can affect performance not only in mathematics but also in science, economics, and other subjects. Therefore, the purpose of this study is to identify teacher difficulties regarding the preparation to improve students’ mathematical reasoning through lesson plans. The study is a descriptive study, one of the qualitative research methods. The data was collected via an online form developed by the researchers and included open-ended questions. The participants of this study were ninety-three mathematics teachers who enrolled in a three-week online workshop about improving students’ mathematical reasoning. Data were analyzed according to the content analysis steps, which is one of the qualitative research methods. It was found that 73,1% of teachers responded that the content load of the curriculum was a major obstacle during planning the lesson to improve students’ mathematical reasoning. And several obstacles are discussed in this paper.